Production of bacterial ?-amylase by B amyloliquefaciens under solid substrate fermentation - Tanyildizi, M. Saban; Ozer, Dursun; Elibol, Murat (Elsevier, 2007)
Production of a-amylase by Bacillus amyloliquefaciens, under solid substrate fermentation (SSF) was investigated in shaken-culture. The maximum alpha-amylase activity was obtained under the following optimized conditions: corn gluten meal (CGM) 30g/l, yeast extract (YE) 10g/l, agitation rate 150 rpm and fermentation temperature 33 degrees C. The results showed that alpha-amylase production in a medium with CGM was five times higher than that in the medium contained starch and other components. The temperature of fermentation was found to be most crucial factor in alpha-amylase production. (C) 2007 Elsevier B.V. All rights reserved.
Keywords: solid substrate fermentation; corn gluten meal; B. amyloliquefaciens; alpha-amylase